Melatonina como antioxidante na criopreservação de sêmen de Brycon orbignyanus (Valenciennes, 1850) - Palhares, Priscila Cotta (2018)
The objective was to improve the semen freezing protocol for piracanjuba, using different freezing curves and melatonin-containing solutions. This study was divided into two stages. The first, consisted of the evaluation of cryopreserved semen in solutions containing different concentrations of melatonin and at different residence times in a nitrogen vapor canister. The second evaluated the semen diluted at the same melatonin concentrations as the first stage solutions, however, they were frozen in two different curves: one using a dry shipper and another using a freezing machine. Semen collections were carried out at Cemig Fish Farming Stations in Volta Grande and Itutinga during the piracema periods in 2016-2017 and 2017-2018. Semen was characterized by observation of volume, appearance, coloration, vigor and sperm concentration. The parameters used to evaluate sperm cell quality were motility rate and duration, plasma membrane integrity, morphology, oxidative profile and fertilization and hatching rates. The oxidative profile variables were evaluated using the Graph pad prism 6.0 program and the other variables of the experiment were analyzed with the aid of the R statistical program. of variance (one-way ANOVA). Means were compared by Tukey test when significant effect was found (p <0.05). In the first stage, only for the fertilization rate was observed statistically significant difference (p <0,05) in the interaction between the solutions and the times in the dry shipper. The M2 solution presented the best results in relation to the control solution, for the parameters of vitality, motility rate, motility times and progressive motility (85.2 ± 2.8%, 64.63 ± 8.3%, 84, 22 ± 11.4 sec, 17.01 ± 1.2%). In the second stage, a difference (p <0.05) was observed between the solutions in the parameters of vitality, morphology, motility and fertilization rates. Melatonin solutions presented the best values. In oxidative stress, only lipid peroxidation and SOD activity showed differences (p <0.05) in the curve and solution interaction, showing the solutions with the lowest values. It was concluded that the addition of melatonin at a concentration of 2 mM, associated with the cryoprotectant methylglycol in the freezing solution, improved the sperm quality, regardless of the curves used.